Preparation, Optimization and Activity Evaluation of PLGA/Streptokinase Nanoparticles Using Electrospray - Nasrin Yaghoobi; Reza Faridi Majidi; Mohammad ali Faramarzi; Hadi Baharifar; Amir Amani (Tabriz University of Medical Sciences, 2017)
Purpose: PLGA nanoparticles (NPs) have been extensively investigated as carriers of different drug molecules to enhance their therapeutic effects or preserve them from the aqueous environment. Streptokinase (SK) is an important medicine for thrombotic diseases. Methods: In this study, we used electrospray to encapsulate SK in PLGA NPs and evaluate its activity. This is the first paper which investigates activity of an electrosprayed enzyme. Effect of three input parameters, namely, voltage, internal diameter of needle (nozzle) and concentration ratio of polymer to protein on size and size distribution (SD) of NPs was evaluated using artificial neural networks (ANNs). Optimizing the SD has been rarely reported so far in electrospray. Results: From the results, to obtain lowest size of nanoparticles, ratio of polymer/enzyme and needle internal diameter (ID) should be low. Also, minimum SD was obtainable at high values of voltage. The optimum preparation had mean (SD) size, encapsulation efficiency and loading capacity of 37 (12) nm, 90% and 8.2%, respectively. Nearly, 20% of SK was released in the first 30 minutes, followed by cumulative release of 41% during 72 h. Activity of the enzyme was also checked 30 min after preparation and 19.2% activity was shown. Conclusion: Our study showed that electrospraying could be an interesting approach to encapsulate proteins/enzymes in polymeric nanoparticles. However, further works are required to assure maintaining the activity of the enzyme/protein after electrospray.